Evaluation of design criteria for mini unmanned aircraft systems (UAS) applications. Issue 3 (20th October 2021) - P.S., Ramesh; J.V., Muruga Lal Jeyan
Abstract : Purpose: This paper aims to evaluate the factors that dictate the design of a mini unmanned aircraft system (UAS). Design/methodology/approach: This paper analyses various dimensions that dictate the design criteria for a mini UAS. Findings: Compared to civil applications, design of mini UAS for military application is much more challenging owing to combat restrictions. Topics related to civil applications dominate research in the field of mini UAS, with over 60% of the papers accounting for civil applications. Limited published articles related to military applications are available. While 86% of the in-production mini UAS is primarily meant for military applications, only 9% of the research is devoted to military applications of mini UAS. Most mini UAS, although designed primarily for military applications, are also extensively used for various civil applications. Critical aspects that influence the employment of mini UAS in the tactical battlespace are area of interest, type of operation, type of operational tasks, terrain and network-centric operations. All these factors collectively impact the design of a mini UAS. Practical implications: According to various studies, mini UAS is the fastest growing segment amongst all classes of UAS. This paper will provide vital inputs to the designers and manufacturers of mini UAS for both military and civil applications. Social implications: Mini UAS are in the list of "must-have" for modern militaries across the world and is also growing exponentially in the civil domain. Therefore, it is important to understand the critical factors that dictate the design of mini UAS. Originality/value: To the best of the authors' knowledge, such an analysis is not available in the open domain.